Catalytic Reductive Amination of Aldehydes and Ketones With Nitro Compounds: New Light on an Old Reaction - Sukhorukov, Alexey Yu. (Frontiers in Chemistry, 2020)
Reductive amination of carbonyl compounds with primary amines is a well-established synthetic methodology for the selective production of unsymmetrically substituted secondary and tertiary amines. From the industrial and green chemistry perspective, it is attractive to combine reductive amination with the synthesis of primary amines in a single one-pot catalytic process. In this regard, nitro compounds, which are readily available and inexpensive feedstocks, received much attention as convenient precursors to primary amines in such processes. Although the direct reductive coupling of nitro compounds with aldehydes/ketones to give secondary and tertiary amines has been known since the 1940's, due to the development of highly efficient and selective non-noble metal-based catalysts a breakthrough in this area was made in the last decade. In this short overview, recent progress in the methodology of the reductive amination with nitro compounds is summarized together with applications to the synthesis of bioactive amines and heterocycles. Remaining challenges in this field are also analyzed.